Oxidative stress response elicited by mitochondrial dysfunction: implication in the pathophysiology of aging - Wang, Chih-Hao; Wu, Shi-Bei; Wu, Yu-Ting; Wei, Yau-Huei (Experimental biology and medicine (Maywood, N.J.), 2013)
Under normal physiological conditions, reactive oxygen species (ROS) serve as 'redox messengers' in the regulation of intracellular signalling, whereas excess ROS may induce irreversible damage to cellular components and lead to cell death by promoting the intrinsic apoptotic pathway through mitochondria. In the aging process, accumulation of mitochondria DNA mutations, impairment of oxidative phosphorylation as well as an imbalance in the expression of antioxidant enzymes result in further overproduction of ROS. This mitochondrial dysfunction-elicited ROS production axis forms a vicious cycle, which is the basis of mitochondrial free radical theory of aging. In addition, several lines of evidence have emerged recently to demonstrate that ROS play crucial roles in the regulation of cellular metabolism, antioxidant defence and posttranslational modification of proteins. We first discuss the oxidative stress responses, including metabolites redistribution and alteration of the acetylation status of proteins, in human cells with mitochondrial dysfunction and in aging. On the other hand, autophagy and mitophagy eliminate defective mitochondria and serve as a scavenger and apoptosis defender of cells in response to oxidative stress during aging. These scenarios mediate the restoration or adaptation of cells to respond to aging and age-related disorders for survival. In the natural course of aging, the homeostasis in the network of oxidative stress responses is disturbed by a progressive increase in the intracellular level of the ROS generated by defective mitochondria. Caloric restriction, which is generally thought to promote longevity, has been reported to enhance the efficiency of this network and provide multiple benefits to tissue cells. In this review, we emphasize the positive and integrative roles of mild oxidative stress elicited by mitochondria in the regulation of adaptation, anti-aging and scavenging pathway beyond their roles in the vicious cycle of mitochondrial dysfunction in the aging process.